The First and Fiftieth Years of Independent Burma's Law Reports - Zan, Myint (Victoria University of Wellington Law Review, 2004)
This article compares the annual Law Reports of the first year of Burmese independence in 1948 with those published in the fiftieth year of Burmese independence (1998). In making the comparison, the author highlights the fundamental changes that occurred in the structure and composition of the highest courts in Burma, along with relevant background and factors effecting these changes. There was a movement away from the predominant use of English in 1948 towards judgments exclusively in Burmese in the 1998 Law Reports. Burma's neighbours, who shared a common law legal heritage, did not follow this trend after their independence. This shift, combined with Burma's isolation from the rest of the world, makes analysis of Burmese case law from the past three and a half decades very difficult for anyone not proficient in the Burmese language. This article tries to fill the lacunae as far as the Law Report from the fiftieth year of Burma's independence is concerned.